2016
DOI: 10.1111/nep.12732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of birth weight on adulthood renal function: A bias‐adjusted meta‐analytic approach

Abstract: While the association between low birth weight (LBW; <2500 g) and development of adult chronic renal disease (CKD) is inconsistently reported, less information is available regarding association of high birth weight (HBW; ≥4000 g) with CKD. We undertook a systematic review and meta-analysis on studies published before 30 September 2015 and report associations between birth weight and renal function. Blood [Glomerular filtration rate (GFR)] and urine [Microalbuminuria/Albumin excreation rate (AER)/urinary album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 88 publications
(518 reference statements)
4
22
1
2
Order By: Relevance
“…Analysis of the collected findings indicated that very LBW (<1500g) individuals had a greater subsequent risk for development of CKD, determined by albumin/protein excretion, serum creatinine level, creatinine clearance, GFR or presence of ESRD, compared to normal birth weight counterparts (25). Das et al noted similar findings in a study published in 2016 (24). In this systemic review and meta-analysis of studies published prior to September 2015, LBW was associated with lower GFR (24).…”
Section: Epidemiological Studies Linking Birth Weight and Renal DIsupporting
confidence: 72%
See 2 more Smart Citations
“…Analysis of the collected findings indicated that very LBW (<1500g) individuals had a greater subsequent risk for development of CKD, determined by albumin/protein excretion, serum creatinine level, creatinine clearance, GFR or presence of ESRD, compared to normal birth weight counterparts (25). Das et al noted similar findings in a study published in 2016 (24). In this systemic review and meta-analysis of studies published prior to September 2015, LBW was associated with lower GFR (24).…”
Section: Epidemiological Studies Linking Birth Weight and Renal DIsupporting
confidence: 72%
“…Das et al noted similar findings in a study published in 2016 (24). In this systemic review and meta-analysis of studies published prior to September 2015, LBW was associated with lower GFR (24). In addition, over one third of those with diabetes had LBW and CKD, defined by GFR and the microalbuminuria/albumin excretion rate ( AER ) /urinary albumin creatinine ratio ( ACR ) (23).…”
Section: Epidemiological Studies Linking Birth Weight and Renal DIsupporting
confidence: 72%
See 1 more Smart Citation
“…However, another two studies revealed no difference in telomere length according to newborn birthweight (Akkad et al, 2006;Entringer, Epel, Lin, Blackburn, Buss, Shahbaba, et al, 2015;Entringer, Epel, Lin, Blackburn, Buss, Simhan, et al, 2015). Short telomere lengths are associated with increased risks of chronic diseases in adults (Agmon-Levin et al, 2013;Ma et al, 2011;Wang, 2016), and a low birthweight (<2,500 g) increases the risk of chronic diseases such as chronic kidney disease (Das et al, 2016), asthma (Xu et al, 2014), and coronary heart disease (Wang et al, 2014) (Ramakrishnan, Imhoff-Kunsch, & Martorell, 2014). A recent meta-analysis concluded that providing nutritional advice or balanced energy and protein supplements to pregnant women may be beneficial (Ota, Hori, Mori, Tobe-Gai, & Farrar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that low nephron number is associated with renal disease in adulthood, [8][9][10][11] with a multitude of animal studies identifying that a 20%-30% reduction in nephron number is important. [12][13][14][15] Precise and accurate estimation of nephron number by noninvasive methods is not currently feasible, although a direct relation between foetal weight and kidney size, 16 birth weight and kidney function, 17,18 and between kidney mass and total nephron number 19,20 has been reported. As renal mass is proportional to renal volume in infants, kidney volume is currently considered a surrogate measure of nephron number.…”
Section: Introductionmentioning
confidence: 99%